Merging systems engineering methodologies with the Agile Scrum framework for Department of Defense software projects - Rosson, Dallas, author; Bradley, Thomas, advisor; Batchelor, Ann, advisor; Coleman, David, committee member; Eftekhari Shahroudi, Kamran, committee member; Wise, Dan, committee member (Colorado State University. Libraries, 2024)
Only large-scale Department of Defense (DoD) software projects executed under the direction of the DoD Instruction 5000.2, Operation of the Adaptive Acquisition Framework, are required to follow rigorous systems engineering methods. Many software projects lack the benefits of established systems engineering methodologies and good engineering rigor and fail to meet customer needs and expectations. Software developers trained in the use of the various Agile frameworks are frequently strongly opposed to any development methodology that could be viewed as infringing on the principles of the Agile Manifesto. Agile projects, by their nature, embrace the concept of change, but uncontrolled change leads to project failures whereas controlled change can lead to sustained and innovative forward progress. In order to improve the results of these vital software projects, Department of Defense (DoD) software projects require a methodology to implement systems engineering rigor while still employing Agile software practices. The Agile Scrum framework alone is not rigorous enough to fully document customer needs as User Stories are written tracking only who, what, and why at a non-atomic level and commonly never looked at again after development needs are met. Systems engineering methods alone are not flexible enough to take advantage of the inherent nature to change capability required in software projects, which require flexibility in schedule and requirements. A new methodology, the Systems Engineering Focused Agile Development method, takes a rigor-flexibility-rigor approach to development and makes use of the strengths of the Agile Scrum framework with the best practices of systems engineering methodologies resulting in a common language that better allows cross-functional teams to communicate project needs while also allowing software developers to maintain flexibility in the execution of software projects. This research has determined that the thoughtful blending of Agile systems engineering and modern systems engineering methods has the potential to provide DoD software projects with benefits to cost, schedule, and performance.
Keywords: Department of Defense; software engineering; Agile; systems engineering; Scrum